Performance analysis of RTS/CTS protocol over basic access in wireless networks: Study of protocol impact on performance in wireless networks - Kuruvilla, Mathew; Issac, B.; Eng, Tan Chong (Institute of Electrical and Electronics Engineers Inc., 2015)
The CSMS/CA protocol is employed in wireless networks in order to overcome issues such as the hidden node problem. This mechanism is expected to handle collisions better using the RTS/CTS mechanism. This method will allow a participating node to take part in communication only if it receives a "Clear to Send" message and thereby, theoretically "avoiding" collision. The objective of this paper is to analyse the improvement that the RTS/CTS mode brings over the Basic Access mode. The paper presents the study of wireless nodes within a specific area with increasing node concentration to verify the performance impact of a protocol in wireless networks, particularly when the node concentration increases.